STRATIGRAPHIC REVISION OF THE EOCENE ALBIDONA FORMATION IN THE TYPE LOCALITY (CALABRIA, SOUTHERN ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2000)
Original biostratigraphic and sedimentologic data concerning the type-section of the Albidona Formation (Liguride Complex, Southern Apennines, Italy) are presented and discussed. Since its definition in 1962, this lithostratigraphic unit has been the object of controversial interpretations in terms of age attribution and paleotectonic significance. Based on cross-observations performed on calcareous nannofossils and palynomorphs, we conclude that the Albidona Formation must be assigned to the Eocene and, based on these evidences, we make a review of the previous biostratigraphic literature. We further recognise four different turbidite systems (named A to D), bounded by minor stratigraphic hiatuses, that are characterised by different sedimentary facies assemblages and petrofacies. The overall vertical arrangement demonstrates that the Albidona Formation was deposited in a tectonically mobile basin during a phase of deformation that is older than the apenninic deformation and must be likely referred to the alpine tectonics of the Calabrian arc. Moreover, the relationship with the underlying folded unit suggests for the Albidona Formation the significance of an episutural deposit relevant to a Paleogene deformation that affected the older units of the Liguride Complex. By considering stratigraphic and sedimentological features, we suggest a correlation of the Albidona Formation with analogue turbidite suites cropping out in the Apennines, discussing their significance in the context of the Eocene tectonic paroxysm in the Mediterranean area.